Regarding the role of rock paintings in studying the spiritual and religious life of ancient people - Bakhodir, Tugalov Boburjon; Kahramon, Ummatov Sardar; Toir, Bozorova Maftuna (PT. Antis International Publisher, 2024)
In this article, an attempt was made to reveal information about the role of stone paintings in the study of the spiritual and religious life of ancient people based on the data studied and scientifically analyzed by scientists